If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 15 = 77 Reorder the terms: 15 + 2x = 77 Solving 15 + 2x = 77 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 2x = 77 + -15 Combine like terms: 15 + -15 = 0 0 + 2x = 77 + -15 2x = 77 + -15 Combine like terms: 77 + -15 = 62 2x = 62 Divide each side by '2'. x = 31 Simplifying x = 31
| x+4(x-5)=4(x-2) | | 7y+10x=43.70 | | 9-c=-2 | | 100+2.9x=30 | | 3-2p=-7+4p | | 5b^2+6b+1=0 | | 2x/5+3=7 | | 25k^2-1=0 | | 8-2z/52=10/13 | | 7x-3y=10fory | | 2a+3a+3x+4y= | | 2(4x-9)=15-4x | | 3n+8=-10 | | -3a+29=5(a-2)+23 | | 8x+11=6-3x | | (7x-8)(3x+2)= | | -3(5x-11)=138 | | 7(2x+3)-12x=3x+17 | | -8n=32 | | 0.15x+0.05(20-x)=0.10(22) | | 2x^2-5x+3=3 | | 0.80x+20.00=100 | | 2(10m-7a)+3(8a-3m)= | | 7(3x+4+2x)=63 | | 0.80x+20.00=281.60 | | y=-9/7x+2 | | x+14=29 | | 0=-100+(.7q-6)q | | 2(22-3*7)= | | 28-16=3(x-1) | | b+a=cx | | 2(x+6)=12+2x |